Integrated Marketing Communication Strategy at Events Atlas First Anniversary “Tyga” - Simamora, Richard; Suryawati , I Gusti Agung Alit; Pradipta, Ade Devia (Jurnal Pewarta Indonesia, 2025)
Atlas Beach Fest is one of the popular beach clubs in the Canggu area and is known as the largest beach club in the world. Californian rapper Michael Ray Stevenson, known by his stage name Tyga (Thank You God Always), was invited to commemorate the first anniversary of Atlas Beach Fest on August 5, 2023. The promotion carried out by Atlas Beach Fest Bali in attracting public interest is evidenced by the number of spectators who reached 30,000 audiences. The activities carried out by Atlas in expanding marketing require the right and effective strategy. The purpose of this study is to review and provide an explanation related to the integrated communication strategy used by Atlas Beach Fest Bali in the Atlas First Anniversary "Tyga" event. This study uses a descriptive qualitative approach with a post-post-positivism paradigm. This study uses a purposive sampling technique to determine informants. Data were obtained from interviews, observations, and documentation. The results of this study show that 7 elements from the integrated marketing communication strategy (advertising, sales promotion, direct marketing, personal selling, public relation, event, and word of mouth) carried out by Atlas Beach Fest at the Atlas First Anniversary event ''Tyga'' is successful in an effort to win the competition of the entertainment industry in the Canggu area. Atlas Beach Fest must remain consistent in using events as part of its integrated marketing communications (IMC) strategy to become better known to the public and the entertainment world.